2020
DOI: 10.3390/ijerph17239150
|View full text |Cite
|
Sign up to set email alerts
|

Realtors’ Perceptions of Social and Physical Neighborhood Characteristics Associated with Active Living: A Canadian Perspective

Abstract: Realtors match home-seekers with neighborhoods that have built and social characteristics they desire to pursue active lifestyles. Studies have yet to explore realtors’ perspectives on neighborhood design that supports active living. Using qualitative description, our study was to explore the perceptions and understandings of neighborhood design (walkability, healthy, bike-ability, vibrancy, and livability) among urban residential realtors. Nineteen (6 men; 13 women; average age 48 years) self-identified resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Publically available tools, such as Walk Score ® , Bike Score ® , and Transit Score ® (available on real estate sites such as Redfin: https://www.redfin.com/ ) may be useful for identifying new neighborhoods that can support preferences for transport-related physical activity. Moreover, real estate professionals may play an important role in matching home-seekers with neighborhoods that include built characteristics that support their walking preferences ( 67 69 ). More importantly, our findings highlight the need for urban development and planning authorities, municipalities, and land developers to increase the supply of newly developed walkable neighborhoods and invest in the redevelopment of existing neighborhoods to increase their supportiveness for transportation walking.…”
Section: Discussionmentioning
confidence: 99%
“…Publically available tools, such as Walk Score ® , Bike Score ® , and Transit Score ® (available on real estate sites such as Redfin: https://www.redfin.com/ ) may be useful for identifying new neighborhoods that can support preferences for transport-related physical activity. Moreover, real estate professionals may play an important role in matching home-seekers with neighborhoods that include built characteristics that support their walking preferences ( 67 69 ). More importantly, our findings highlight the need for urban development and planning authorities, municipalities, and land developers to increase the supply of newly developed walkable neighborhoods and invest in the redevelopment of existing neighborhoods to increase their supportiveness for transportation walking.…”
Section: Discussionmentioning
confidence: 99%
“…McCormack et al . (2020) found that cycling can be a controversial topic, and that issues surrounding built form, healthy lifestyle, and education can attract or deter interest in cycling. While a focus on measuring property value impact is significant, it ultimately ignores external factors that could influence public perceptions, creating a gap in our understanding of why public resistance towards cycling infrastructure exists when property values are positively impacted.…”
Section: The Role Of Cycling Infrastructure In Changing Property Valu...mentioning
confidence: 99%
“…In addition, qualitative research has begun to examine the home-buying process through the lens of realtors and developers, including their agency as stakeholders in the market (Carnoske et al 2010;Kern 2016;McCormack et al 2020). McCormack et al (2020 found that cycling can be a controversial topic, and that issues surrounding built form, healthy lifestyle, and education can attract or deter interest in cycling.…”
Section: The Role Of Cycling Infrastructure In Changing Property Valu...mentioning
confidence: 99%
See 2 more Smart Citations